Non-Verbal Communication and Volleyball: A New Way to Approach the Phenomenon - Raiola, Gaetano; Tore, Alfredo Di (Richtmann Publishing, 2012)
Too often in sports the qualitative aspects of performance are addressed with superficially and approximation becauseit believes that it is not scientifically possible to explain everything that is not easily quantifiable and expressible in the form ofnumbers. In volleyball, the ball is rejected, both among members of a team and between the two opposing teams, with afrequency significantly greater than in other team sports. For this reason, in volleyball, not immediately quantifiable aspects ofthe game action are greater than other team sports. The qualitative aspects in volleyball concern technical skills, tacticaldecisions, strategy and more. Among these, non-verbal communication has not yet been considered as an object of study andthus not yet investigated. This study provides the initiation of an integrated research between social science and sports scienceto allow technicians, coaches and physical education teachers to learn more about another important aspect of quality for thepurposes of training and education. The aim is to identify applications of the principles of nonverbal communication, which hasits own epistemological framework, to volleyball through the systematic analysis of specific game situations. The methodintegrates the theoretical-argumentative and descriptive approach. Communicative events attributable to non-verbalcommunication were classified into three categories: communication tactics, functional communication and diagnosticcommunication. The frequency and outcome of these events were investigated in relation to three specific volleyball technicalskills related to nonverbal communication: a) the second ball goes to the opposite court instead of setting for attacking; b) theattack as fast as possible in the middle of the net; c) the off speed hit instead of power spike over the block; The results show asignificant incidence of communicative events related to non-verbal communication on the final outcome and, therefore, suggestthat non-verbal communication is subject of interest to technicians, coaches and physical education teachers